Kepemimpinan Kyai Dalam Konsep Primal Leadership Di Pondok Pesantren Mansyaul Ulum Nagasari Congkop - Jamil, Subhal (Al-Abshar: Journal of Islamic Education Management, 2024)
Islamic boarding schools are educational institutions whose main mission is to produce the next generation of the nation with noble morals, of course the leadership of a kyai in an Islamic boarding school is very important. Islamic boarding schools are one of the safe and comfortable places for learning and are able to attract the interest of teenagers to study in them. For that, the function of leadership management in Islamic boarding schools is very important to apply. This research will focus on how the leadership management of a kyai in improving the emotional intelligence of students at the Mansya'ul Ulum Congkop Islamic boarding school. This study uses a qualitative approach with a field method, data is collected using observation and interview techniques and is supplemented with several reference books as supporting data. The results of this study indicate that the leadership management of kyai in the Mansyaul Ulum Islamic boarding school in terms of planning, organizing, controlling management functions has been implemented well. Increasing the emotional intelligence of students at the Mansya'ul Ulum Congkop Islamic boarding school is also influenced by good leadership management. Therefore, the professionalism of a kyai's leadership in running the wheels of Islamic boarding school leadership, especially in the movement, has a very important role. A kyai is required to be able to foster a spirit of learning and always motivate the students in every activity in the Islamic boarding school, not only to carry out their obligations but more than that, their emotional intelligence also needs to be truly achieved based on socio-religious principles